2021
DOI: 10.1111/1541-4337.12793
|View full text |Cite
|
Sign up to set email alerts
|

Whey allergens: Influence of nonthermal processing treatments and their detection methods

Abstract: Whey and its components are recognized as value-added ingredients in infant formulas, beverages, sports nutritious foods, and other food products. Whey offers opportunities for the food industrial sector to develop functional foods with potential health benefits due to its unique physiological and functional attributes. Despite all the above importance, the consumption of whey protein (WP) can trigger hypersensitive reactions and is a constant threat for sensitive individuals. Although avoiding such food produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 211 publications
0
8
0
Order By: Relevance
“…5 Besides, the immunoglobulin G (IgG)/ IgE-binding capacity of food allergens was reduced by highpressure, ultrasonic, and irradiation treatment as a result of the secondary structure being changed and non-covalent bonds being destroyed. 11 The structure and activity of allergen are closely related. 12 Chemical denaturants were used to study the conformation−activity relation of protein.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Besides, the immunoglobulin G (IgG)/ IgE-binding capacity of food allergens was reduced by highpressure, ultrasonic, and irradiation treatment as a result of the secondary structure being changed and non-covalent bonds being destroyed. 11 The structure and activity of allergen are closely related. 12 Chemical denaturants were used to study the conformation−activity relation of protein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have found that the enzyme cross-linking reaction and Maillard reaction could reduce the immunoreactivity of Scy p 4, which is due to Scy p 4 being modified to change its structure . Besides, the immunoglobulin G (IgG)/IgE-binding capacity of food allergens was reduced by high-pressure, ultrasonic, and irradiation treatment as a result of the secondary structure being changed and non-covalent bonds being destroyed . The structure and activity of allergen are closely related .…”
Section: Introductionmentioning
confidence: 99%
“…Heat and acid-alkali are important factors that induce structural variations of allergic proteins during food processing, like boiling, roasting, fermentation, and others. 34,35 The thermal and pH resistance of P. trituberculatus SCP were assessed with rSCP through immunologic approaches. The rSCP retained main bonds and strong immunoreactivity in normal conditions, yet partially degraded at extreme conditions (temperature >80 °C and pH 1−2).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Heat and acid-alkali are important factors that induce structural variations of allergic proteins during food processing, like boiling, roasting, fermentation, and others. , The thermal and pH resistance of P. trituberculatus SCP were assessed with rSCP through immunologic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, detection of allergens is also a possible application of the CRISPR‐Cas system. Currently, immunological and DNA‐based analyses are commonly used to detect allergenic proteins in foods (Khan et al., 2021). Mass spectrometry and aptamer‐based biosensors have also been used as preliminary techniques for detection.…”
Section: Applications Of Crispr‐cas‐based Detection In Food Safety Mo...mentioning
confidence: 99%